Geometria no 9º ano : uma abordagem dinâmica - Silva, Rodrigo Nicolino da (2020)
With the main objective of diversifying the ways of explaining the contents of Euclidean geometry, we present a proposal for a dynamic approach, focusing on the student’s lear- ning through what he is seeing, experiencing, testing and knowing, valuing the empirical process in which the experience will bring the understanding and the conviction of certain properties. We inform that the idea “dynamic approach”, used in this work, is strictly lin- ked to the discoveries that happen through movements made in geometric figures or parts of them with the aid of software. Here we have 14 activities with dynamic approaches made through the GeoGebra software, which were elaborated for several topics consulted in mathematics textbooks of Elementary School II that are in conformity with the BNCC (National Common Curricular Base). We present a summary table, containing the skills and competences required by the BNCC of the contents of Euclidean geometry, as well as observations on these in relation to the use of GeoGebra in classes. In each activity we describe examples of how to use GeoGebra in definitions, explanations of contents and demonstrations of properties or theorems present in geometric figures. We describe some characteristics of the use of the blackboard and of GeoGebra in classes, making a comparison between the two resources. We present some reasons for choosing GeoGebra and provide an electronic address where you can download it and find more information about this software that is free, open source, easy to use and contains several resources, which were necessary to fulfill our objectives.